2018
DOI: 10.1186/s12864-018-5211-y
|View full text |Cite
|
Sign up to set email alerts
|

RRAD, IL4I1, CDKN1A, and SERPINE1 genes are potentially co-regulated by NF-κB and p53 transcription factors in cells exposed to high doses of ionizing radiation

Abstract: BackgroundThe cellular response to ionizing radiation involves activation of p53-dependent pathways and activation of the atypical NF-κB pathway. The crosstalk between these two transcriptional networks include (co)regulation of common gene targets. Here we looked for novel genes potentially (co)regulated by p53 and NF-κB using integrative genomics screening in human osteosarcoma U2-OS cells irradiated with a high dose (4 and 10 Gy). Radiation-induced expression in cells with silenced TP53 or RELA (coding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…p53 knockdown, as expected, mitigates (whereas RelA silencing enhances) radiation-dependent PAI-1 expression (107). Because p300-cAMP response element binding protein-binding protein (CBP) coactivator complexes mediate expression of genes competitively regulated by both p53 and RelA, 1 model suggests that RelA interactions with p300-CBP may inhibit target gene expression, whereas binding of p53 to p300-CBP results in loss of (suppressive) NF-kB activity (107,108). Gain-offunction p53 variants also promote acquisition of the fibroproliferative phenotype by complexing with and suppressing the activity of the PAI-1-CD44-cyclin D1 transcriptional repressor Kruppel-like factor 17 (109).…”
Section: P53 Is Required For Expression Of a Subset Of Tgf-b1 Profibrsupporting
confidence: 80%
See 1 more Smart Citation
“…p53 knockdown, as expected, mitigates (whereas RelA silencing enhances) radiation-dependent PAI-1 expression (107). Because p300-cAMP response element binding protein-binding protein (CBP) coactivator complexes mediate expression of genes competitively regulated by both p53 and RelA, 1 model suggests that RelA interactions with p300-CBP may inhibit target gene expression, whereas binding of p53 to p300-CBP results in loss of (suppressive) NF-kB activity (107,108). Gain-offunction p53 variants also promote acquisition of the fibroproliferative phenotype by complexing with and suppressing the activity of the PAI-1-CD44-cyclin D1 transcriptional repressor Kruppel-like factor 17 (109).…”
Section: P53 Is Required For Expression Of a Subset Of Tgf-b1 Profibrsupporting
confidence: 80%
“…Interestingly, in a different cell type, g-radiation also stimulates PAI-1 expression as well as the binding of p53 and the avian reticuloendotheliosis oncogene homolog A (RelA) (p65) to the PAI-1 gene. p53 knockdown, as expected, mitigates (whereas RelA silencing enhances) radiation-dependent PAI-1 expression (107). Because p300-cAMP response element binding protein-binding protein (CBP) coactivator complexes mediate expression of genes competitively regulated by both p53 and RelA, 1 model suggests that RelA interactions with p300-CBP may inhibit target gene expression, whereas binding of p53 to p300-CBP results in loss of (suppressive) NF-kB activity (107,108).…”
Section: P53 Is Required For Expression Of a Subset Of Tgf-b1 Profibrmentioning
confidence: 54%
“…The transcription factor p53 is known to control radiation sensitivity [25,26,27,28]. Except in a few reports, p53 dysfunction has been shown to correlate with reduced radiosensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Although the relationship between p53 and the radiation response is well-known [25,26,27,28], p53 is not the only factor that controls the radiosensitivity of cells. Previous studies have suggested that 15-LOX-2 and 12-LO are also involved in regulating radiosensitivity both in head and neck and prostate cancers [22,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of Price et al ( 2015 ) suggests that CDKN1A regulates Langerhans cell and could influence the response of cutaneous tumours to radiotherapy. CDKN1A abnormal expression has been reported to be associated with acute sensitivity to radiation (Amundson et al 2003 ; Badie et al 2008 ; Szołtysek et al 2018 ). In Alsbeih et al ( 2007 ), they show that individual response in CDKN1A is related to inherent radiosensitivity.…”
Section: Introductionmentioning
confidence: 99%